2015
DOI: 10.18632/oncotarget.2934
|View full text |Cite
|
Sign up to set email alerts
|

Circulation long non-coding RNAs act as biomarkers for predicting tumorigenesis and metastasis in hepatocellular carcinoma

Abstract: BACKGROUND & AIMSAlpha Fetal Protein (AFP) was one of the traditional biomarker for diagnosis of Hepatocellular carcinoma (HCC) clinically, however, with the low specificity of AFP, the early diagnosis or the metastasis prediction of HCC is inferior. A new, minimally invasive and more specificity biomarker for the diagnosis or metastasis prediction of HCC are necessary.METHODSIn this study, we applied an lncRNA microarray to screen the potential biomarker for HCC. The multi-stage validation and risk score form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 33 publications
1
105
0
Order By: Relevance
“…The lncRNA-CTBP has also been identified had high sensitivity and specificity for discriminating HCC from healthy controls and also from CH patients [29]. Tang et al also published the results that lncRNAs might act as biomarker for the diagnosis of HCC from healthy control and CH patients [30]. In this study, by employing a multiple screening phase, we found that LINC00152, RP11-160H22.5, XLOC014172 and LOC149086 were screened with significant difference in training set.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA-CTBP has also been identified had high sensitivity and specificity for discriminating HCC from healthy controls and also from CH patients [29]. Tang et al also published the results that lncRNAs might act as biomarker for the diagnosis of HCC from healthy control and CH patients [30]. In this study, by employing a multiple screening phase, we found that LINC00152, RP11-160H22.5, XLOC014172 and LOC149086 were screened with significant difference in training set.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a novel biomarker for diagnosing HCC at early stage is intensively desired in clinical. Over the past decade, numerous studies were undertaken to explore the biomarker for HCC [30]. However, the research progress remains quite slow.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple evidence have suggested that ncRNAs played important roles in a variety of biological processes. LncRNAs act as a regulator of gene expression and are closely associated with the development of many diseases, especially malignant tumors [4-7]. …”
Section: Introductionmentioning
confidence: 99%